A comparative study of horizontal and vertical architectural design studio management - Abdullah, Fadzidah; Abdul Rahim, Asiah; Wok, Saodah (Common Ground Publishing LLC, 2010)
The Department of Architecture, Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM), had had conducted a horizontal studio management system for the last 11 years of its operation. The same system has also been used by most of the schools of architecture through out the globe. However, due to the increasing numbers of students, and shortage of lecturers, the department had some difficulties in managing the smooth running of architectural design studio teaching. Therefore, the department resolves such problems by introducing a new vertical studio management system, which commenced in December 2008. The implementation of vertical studio system is for the purpose of improving both lecturers-students interaction, and students’ learning capabilities. This research aims to compare the strengths, weaknesses, and effectiveness of two (2) systems of studio management: Horizontal and Vertical Studio Management. With support of survey and interview, this research mainly utilizes action research, in which personal experience of academic staff and students in dealing with both horizontal and vertical studio management systems is documented. It is expected that the new vertical system have some disadvantages as its introduction has not been properly tested and securitised prior to its implementation.